Synthesis and structural characterization of homochiral homo-oligomers of cis-gamma-methoxy-substituted cis- and trans-furanoid-beta-amino acids - Giri, Awadut G.; Jogdand, Ganesh F.; Rajamohanan, Pattuparampil R.; Pandey, Sunil K.; Ramana, Chepuri V. (European Journal of Organic Chemistry, 2012)
Herein we describe the synthesis of cis-/trans-3-aminotetrahydrofuran-2-carboxylic acids (cis-/trans-FAA) having a ?-methoxy group cis to the amine. The homo-oligomers of these two diastereomeric FAAs have been prepared. Preliminary investigation of their solution secondary structures revealed that they are the same as the homo-oligomers of the parent cis-/trans-FAA with the methoxy group only being a spectator substituent.
Keywords: Amino acids; helical structures; Oxygen heterocycles; Peptides